2014
DOI: 10.4311/2013mb0116
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Microbes from Organic Rich Materials: Case Study of Bat Guano from Caves in Romania

Abstract: Cave air, bat guano, and swabs of bat fur from caves with bat guano in Romania were analyzed by using RIDAHCOUNT cultivation plates and standard selective media for Staphylococcus and Streptococcus. 7 CFU/g). The gravity-settling principle was applied to sample airborne microorganisms, and a new method was developed for evaluation of aerosolization potential. In cave air, the concentration of total bacteria was higher than yeast and molds. In addition to coliforms, enterobacteria, E. coli, and unidentified cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Overall, our results show that the external microbial communities on bats follow similar local and regional-scale bacteria patterns as noted in the eastern China soils study (Ma, et al, 2016), bat fecal and internal microbiome studies (Daniel et al, 2013;Borda et al, 2014;Leigue dos Santos et al, 2014), and share predictors with bat species richness in Arizona and New Mexico (S8). We might expect some of the microbial patterns to be driven by differences in rates of bacterial dispersion.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Overall, our results show that the external microbial communities on bats follow similar local and regional-scale bacteria patterns as noted in the eastern China soils study (Ma, et al, 2016), bat fecal and internal microbiome studies (Daniel et al, 2013;Borda et al, 2014;Leigue dos Santos et al, 2014), and share predictors with bat species richness in Arizona and New Mexico (S8). We might expect some of the microbial patterns to be driven by differences in rates of bacterial dispersion.…”
Section: Discussionsupporting
confidence: 69%
“…In a culture-dependent study by Borda et al (2014), common bacteria found in the air above guano piles included: Chryseomonas, Klebsiella, Micrococcus, Salmonella, Staphylococcus, and Streptococcus. Bacillus, Enterobacter, Enterococcus, Escherichia, Klebsiella, Pantoea, Pseudomonas and Serratia were found in the gut of the short-nosed fruit bat (Daniel et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gravity-settling method (Borda et al, 2014) was used to sample airborne biomass in Postojna Cave. Sterilized limestone tablets with a diameter of 41 mm were exposed to the atmosphere for 34 days, starting on 30 September 2015.…”
Section: Settled Aerosol Samplesmentioning
confidence: 99%
“…The results of bacterial isolation can be seen in Table 2. The number of bacteria on bat guano based on Table 2 were calculated using the formula is 3,347x10 7 cfu/ g. Microorganism diversity in guano fueled by the condition of the guano that has a high temperature and high humidity (96.5% to 99.8%) where that condition can interact with components of guano and provide nutrients for microorganisms reproduction and create a habitat for microorganisms [9].…”
Section: B Isolation Of Bat Guano Bacteriamentioning
confidence: 99%